O novo sindicalismo e a atuação dos professores de Pernambuco durante o regime civil-militar: educação, greves e resistência: (1979-1985). - Nascimento, Marcos Antônio Heliodoro do (2020)
During the period of the Civil-Military Dictatorship in Brazil, installed from 1964 to 1985, there were repressions and even persecution of various aspects by the State in relation to union groups in the country, among them, the groups that represented the category of workers. teachers. Many of the union leaders were persecuted, dismissed, or prevented from running for elected office in their own categories, which led to constant claims of rights, which when not served by the state, culminated in strikes. In this regard, it is of great importance to highlight the role of unions and teachers in the fight for rights during the period of redemocratization in Brazil, and, for this, the exposed work uses bibliographic research, as well as field research, through questionnaires and interviews with teachers who lived at the time, in order to understand the parameter experienced, and thus contribute to a greater clarification of the reality of the time. The research also aims to present historical elements through news in newspapers, official communications and other documents of historical importance, in order to bring reliable information for understanding the theme. With this, the research gathers interviews with members of union leaders of the time, as well as individuals who were faced with the state repression against the class of teachers, and also crosses documentary references that confirm the facts narrated by the interviewees, and, with that, , there is a clear need to register and value the importance of the class of teachers in the process of developing Brazilian unionism, as well as in the process of democratization in the country, and also in the struggle for workers' rights, since this class is has shown, in many ways, to be a pioneer in the reinvention of rights through strikes.